Resolving challenges of monitoring PV systems: a case study for three 1.5 kW generators in Lima, Peru. Issue 1 (1st January 2022) - Berastain, A E; Conde, L A; Angulo, J; Carhuavilca, A M; García, M; Sevillano-Bendezú, M A; Montes-Romero, J; De la Casa, J; Chirinos, L; Töfflinger, J A
Abstract: This paper addresses challenges from monitoring three grid-connected PV systems with different module technologies in Lima, Peru, following the International Electrotechnical Commission (IEC) standards. Missing and erroneous data due to sensor malfunction or partial shadowing can negatively impact the measured data quality. We developed a program to automatically detect erroneous measurements, enhance the data quality, and calculate PV performance parameters following the IEC-61724 standard to resolve these challenges. The program includes mathematical methods to replace faulty or missing measurements. Finally, we present the impact of the algorithms for erroneous data detection, deletion, and correction on performance calculations.